Behavioral Sciences Approach to Empowering Women in Forest Landscape : Diagnostics Toolkit - World Bank (Washington, DC, 2022)
Forests and terrestrial ecosystems play a primary environmental role in climate-change mitigation and adaptation. In many developing countries, forests provide ecosystem services and support the livelihoods of hundreds of millions of people, mainly the poorest and most vulnerable in rural areas. The sustainable management of natural resources can reduce poverty and enhance shared prosperity at the local level. As countries develop Natural Resource Management (NRM) and forest management, it is crucial to ensure that these processes include women in productive, income-generating activities. Men and women access, use, and manage forests differently, as seen in the gendered nature of activities such as gathering forest products, hunting, wood harvesting, and mineral collection. Furthermore, there are persistent gender gaps in access to services, inputs (including credit and financing), markets, value-addition activities, land tenure, representation, and agency. The Forest Carbon Partnership Facility (FCPF) and the World Bank (WB) have outlined a program aimed at promoting gender equality in REDD+ and foresty strategies and implementation. The FCPF is a global partnership of governments, businesses, civil society, and Indigenous Peoples (IPs) focused on reducing emissions from deforestation and forest degradation, forest carbon stock conservation, sustainable forest management, and the enhancement of forest carbon stocks in developing countries, activities commonly referred to as REDD+. This document aims to help task teams and practitioners identify and diagnose factors contributing to gender gaps in sustainable forest projects in FCPF countries by providing nine people-centered research tools based in the behavioral sciences. Such gaps can be rooted in gender norms, roles, and beliefs, attentional limitations, and procedural hassles, among others.